(untitled) (Journal of Forensic Medicine & Toxicology, 2015)
Sudden death cases are regularly encountered by forensic experts. In present study, 30 sudden cardiac death cases were studied for gross and histopathological changes in heart after excluding other causes. Acute myocardial infarction and old infarct changes were found in varying proportion on gross and microscopy. On histological examination hyperaemia of myocardium and hypertrophy of left ventricle were most common findings in acute cases which are nonspecific. Typical infarction changes are not commonly detected in sudden deaths. On microscopic examination congestion and oedema were detected in most cases. Polymorphonuclear cell infiltrate, waviness of fibres, haemorrhages, and loss of striations, hypereosinophilia, coagulative necrosis and fibrosis were found in significant number of cases.